(untitled) (Journal of Natural Language and Linguistics, 2025)
This study investigated the rhetorical visions created by popular love songs through the lens of Fantasy Theme Analysis. By examining the interplay of setting, character, and action themes, the study identifies several recurring narratives that offer insights into the cultural, social, and emotional significance of love in contemporary society. The analysis reveals a multifaceted exploration of love, encompassing both its joys and sorrows. Songs explore the ambivalent nature of love, its transformative power, and the challenges and complexities of relationships. Using rhetorical devices and poetic techniques, the songs convey powerful messages and evoke emotional responses in listeners. The findings of this study have implications for language and literature education and broader cultural and social analysis. By examining the rhetorical visions in popular love songs, teachers can develop engaging and relevant teaching strategies that foster critical thinking, cultural awareness, and a deeper understanding of the human experience.